National movement for good recordkeeping awareness and commitment to archiving in Indonesia - Harry Bawono; Rayi Darmagara; Rio Admiral Parikesit (Universitas Padjadjaran, 2022)
The National Archives of the Republic of Indonesia (ANRI) revealed in 2016 that most government agencies' recordkeeping was inadequate. As a result, ANRI established the National Movement for the Awareness of Good Recordkeeping (GNSTA) to improve the situation. Initially, this movement used social movements as a framework to broaden its formal, emotional, and substantive dimensions. The study aimed to examine the implementation of the GN(S)TA program and consider what actions the program's designers and organizers can take to improve the program's quality. This study conducted from 2017 to mid-2019 used quatlitative methods, specifically case study and unintentional participatory observation techniques, and updated data from 2019 to 2021. This research found that he GN(S)TA program, a state-sponsored social movement model, has success made government agencies recharge their commitment to good records management. Many government agencies participated in this program's success in improving their records management quality after joining the program. That improvement indicated that government agencies' commitment to proper record management has increased based on the perspective of the formal dimension. Unfortunately, the emotional and substantial dimensions fell behind. If this situation persisted, the commitment would be unendurable. The study concludes that this state-sponsored movement program effectively increases the enthusiasm of government agencies. However, it is too focused on the formal dimension.